The long term outcome of patients with unexplained chronic cough. - Yousaf, N; Montinero, W; Birring, S; Pavord, I (2013)
INTRODUCTION: Up to 40% of patients seen in a cough clinic have unexplained chronic cough. The long term outcome of these patients is uncertain. OBJECTIVE: To determine the long-term outcome in patients diagnosed with unexplained chronic cough. METHODS: We have performed a longitudinal study of symptoms, airway inflammation and spirometry in a cohort of patients with unexplained chronic cough diagnosed over 7 years ago. Cough was assessed using a 100 mm visual analogue scale (VAS). At the first and final visit cough reflex sensitivity was assessed as the concentration of inhaled capsaicin at which the volunteer coughed 2 (C2) and 5 times (C5). RESULTS: We identified 42 patients (32 females) with unexplained chronic cough who had been assessed at least 7 years previously and agreed to a further assessment. The mean (SD) duration of cough was 11.5 (4.5) years at the time of their final assessment. Nine patients (21%) had organ specific autoimmune disease and twenty (48%) had a peripheral blood lymphopaenia. Six (14%) patients had complete resolution of symptoms and 11 (26%) had a significant >10 mm improvement in their cough VAS during follow up. Longitudinal spirometry data was available in 30 patients. The median rate of FEV(1) decline was 44 ml/year and four (13%) patients developed a post-bronchodilator forced expiratory volume in 1 s (FEV(1))/forced vital capacity of less than 0.7. FEV(1) decline was similar in patients with persistent cough and those whose cough improved. No other independent predictors of FEV(1) decline were identified. There were no independent predictors of improvement in cough. CONCLUSIONS: Cough persists over time in the majority of patients with unexplained chronic cough. Patients have an increased rate of decline in FEV(1) and a significant minority develop fixed airflow obstruction.